PENGARUH PERCEIVED SERVICE QUALITY, PERCEIVED VALUE, SATISFACTION DAN IMAGE TERHADAP CUSTOMER LOYALTY (STUDI KASUS GARUDA INDONESIA) - Hartono Subagio; Robin Saputra (Institute of Research and Community Outreach - Petra Christian University, 2012)
PT. Garuda Indonesia constitutes an owned airline that was one of the major players in the premium class airline industry in Indonesia. The subject that the writer observes is Consumer behavior, to the influence of perceived service quality and perceived value on customer loyalty with customer satisfaction and airline image of Garuda Indonesia with 200 customer Surabaya-Jakarta route, and vice versa. Analysis SEM Certainly explain the influence of perceived service quality, convenience, and catering will form the corporate image (Airline Image) and perceived value, which in turn affects customer satisfaction and loyalty Garuda Indonesia in the future. The purpose of recommendation writer is for PT. Garuda Indonesia flight airlines to evaluate and maintain the loyalty of its customers with quality service.